Sex, sport and justice: reframing the 'who' of citizenship and the 'what' of justice in European and UK sport policy. Issue 8 (16th November 2016) - Devine, Cathy
Abstract : Universalist claims are often made about sport which is, as a consequence, increasingly written into national and international policy as an entitlement of citizenship or even human right. Further, in most countries physical education (PE) is a compulsory component of children's education, and sport is seen as central to this. Consequently, in the interests of justice sport must aspire to be egalitarian, that is, relevant to and meaningful for boys and men, and girls and women. In this context three fundamental questions are asked in relation to sport: (1) Do all citizens want to participate? (2) Who counts as a citizen? and (3) What are justice and equality? Feminist political and citizenship theory particularly the work of Pateman, Lister and Fraser is used to explore these questions and interrogate the 'who' of citizenship and the 'what' of justice in relation to framing sport policy in Europe and the UK. It is argued that notwithstanding the extensive use of the Council of Europe definition of sport, 1 and despite or even because of the widespread adoption of the language of gender equality and gender mainstreaming, although formal sport citizenship rights might be accorded to all individuals and regarded as gender neutral, this masks a discourse of androcentric sport citizenship. This has captured European and UK sport policy and provision and is hindering further progress towards gender justice in sport and therefore PE. Given the universal and compulsory aspirations of sport particularly within PE, gender justice should be conceptualised not only as cultural recognition, political representation and economic redistribution within the normalised frame of competitive performance sport or 'sport for sports sake'; but also as a critical meta-political remapping and reframing of sport as sport and physical recreation or 'sport for all'.